Activating and optimizing evaporation-processed magnesium oxide passivating contact for silicon solar cells. (August 2019) - Yu, Jing; Liao, Mingdun; Yan, Di; Wan, Yimao; Lin, Hao; Wang, Zilei; Gao, Pingqi; Zeng, Yuheng; Yan, Baojie; Ye, Jichun
Abstract: Irrespective of the success on reduction of contact resistivity, lack of chemical passivation of evaporated metal oxides heavily hinders their applications as passivating contacts, such contacts can be an alternative route for high efficiency and cost effective silicon solar cells. Here, we demonstrate that electron beam evaporated magnesium oxide (MgOx ) thin film can work as a promising electron-selective passivating contact for n -Si solar cells after a post-annealing treatment and an alumina-initiated atomic hydrogenation. 10 nm MgOx on n -Si provided a surface recombination velocity down to 14.9 cm/s while 1 nm MgOx showed a low contact resistivity of 14 mΩ cm 2 . Comprehensive characterizations revealed the formation of Si–O–Mg bonds and the activation of atomic hydrogens were the main reasons for such high-level passivation. A PERC-like dopant-free rear contact was formed by using the 1 nm-MgOx as electron-collector and the 10 nm-MgOx as passivating layer, the resultant solar cells achieved 27% increment in efficiency and 51 mV increase in open-circuit voltage in comparison with reference devices. The ways of improving passivation quality of MgOx and novel design of contact structure open up the possibility of using evaporation-processed metal oxides as effective and low-cost carrier-selective passivating contacts for n -Si photovoltaic devices. Graphical abstract: Effective passivation over c-Si substrates by electron beam deposited MgOx followed by a low-temperature post-annealing and an alumina-initiated atomic hydrogen passivation has been achieved. a PERC-like dopant-free rear contact with 1 nm-MgOx as electron-transporting layer and 10 nm-MgOx as passivating layer was fabricated to underscore the great potential of MgOx passivating contact.Image 1 Highlights: Electron beam deposited MgOx achieved high passivation by post-annealing and alumina-initiated hydrogen passivation. 10 nm MgOx provided a surface recombination velocity down to 14.9 cm/s. The solar cells featured with the PERC-like MgOx contact achieved 15.5% efficiency. The formation of Si–O–Mg bond and hydrogen passivation were the main reasons for the passivation.